Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

6(2 – 3) = 2(3z - 9)


Sagot :

[tex]▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ { \huge \mathfrak{Answer}}▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ ▪ [/tex]

let's solve for z :

  • [tex]6(2 - 3) = 2(3z - 9)[/tex]

  • [tex]6( - 1) = 6z - 18[/tex]

  • [tex] - 6 + 18 = 6z[/tex]

  • [tex]6z = 12[/tex]

  • [tex]z = \dfrac{12}{6} [/tex]

  • [tex]z = 2[/tex]

Answer:

z = 2

Step-by-step explanation:

6(2 - 3) = 2(3z - 9)

12 - 18 = 6z - 18

12 = 6z

2 = z

Hopefully this helped!

Brainliest please?